Flavonoides O-Glicosilados de Erythroxylum campestre, A. St. Hil (Erythroxylaceae) - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The objective of this work was to isolate, purify and structure some flavonoids present in leaves of Erythroxylum campestre, A. St. Hil (Erythroxylaceae). In a recent literature review, few studies on the elucidation of the chemical constituents of the plant were found. The collection was carried out in the Cerrado reserve located in the Campus Henrique Santillo of the State University of Goiás (UEG). The leaves were dried, crushed and macerated with 96% ethanol in which a crude ethanolic extract was obtained, fractionated by filtration using solvents in increasing order of polarity: hexane, dichloromethane, ethyl acetate and methanol. Subsequently, methanolic extract was submitted to classical liquid chromatography (CLC) techniques with the use of sephadex as a stationary phase and methanol as a mobile phase, and reverse phase high performance liquid chromatography (HPLC) using a Luna analytical column (C18 250 mm X 4.6 mm 5μM) and two solutions (Methanol and phosphoric acid solution, pH 2.62) as eluents with flow of 1.0 mL.min-1. This allowed the separation of 8 fractions, identifying by 1H, 13C and 2D NMR the flavonoids: rutin, kaempferol-3- rutinoside, ombuin-3-rutinoside and an unpublished flavonoid.
Keywords: Erythroxylum campestre; A. St. Hil; Erythroxylaceae; Isolamento; Isolamento; Flavonoides; Determinação estrutural; Erythroxylum campestre; A. St. Hil; Erythroxylaceae; Isolation; Flavonoids; Structural determination; CIENCIAS EXATAS E DA TERRA::QUIMICA